The comparative studies on the effect of food on domestic cat, felis catus / Ahmad Yassir Abdul Halim - Abdul Halim, Ahmad Yassir (Faculty of Applied Sciences, 2017)
Domestic cats (Felis catus) which are often called house cat is a small carnivorous mammal that sometimes being kept as indoor pets. A research has been conducted at housing area Kuala Pilah. The study aim is to compare the different types of cat's food and its effect on certain parameter of growth. Two types of food had been used which are Prodiet kibble and traditional type of food (boiled fish mixed with cooked rice). The experiment was conducted for 8 weeks period. All the kittens show increasing trend in weight and length for both types of foods. The initial and final reading for weight and length was obtained and the average range was calculated. Prodiet kibble, weight was μ=0.52kg and length μ=6.5cm as compared to traditional type of food, the average for weight was μ=0.63kg and for length μ=5.83cm. Results show traditional food gives better growth in terms of weight but for length, Prodiet gives better results. This proved through t-test statistical analysis done. From this study, it showed that traditional food is as good as commercial grade kibble as it can also promote a healthy and normal growth for cat.